Fourth Five-Year Plan Tamil Nadu Draft Annual Plan For 1971-72 - Planning Commission (Planning Commission, 1971)
Agricultural and Allied Programmes, Co-Operation and Community Development, Irrigation and Power, Industry and Mining, Transport and Communications, Social Services, Statement Showing The Details of Plan Schemes Under The Various Developmental and Group Heads
Fourth Five-Year Plan Tamil Nadu Draft Annual Plan For 1971-72
Government of Tamil Nadu